Digital Competences in Higher Education Faculty: Levels of Mastery and Training Needs - Pozos Pérez, Katia V. (2018)
Based on a previous model of faculty digital competence in higher education, a mixed sequential study (QUAN+QUAL) was carried out. A multi-stage design is applied to a study focused on detecting needs according to two of the study's objectives: to identify current competences and to establish-prioritize training needs. The population of the study refers to the faculty of university institutions in the Metropolitan Area of Valle de México. A sample of 20 institutions (11 public, 9 private) participates, with 247 professors involved. The results point out to a mid-low mastery of the digital competences corresponding to the teaching role (planning, development, and delivery of learning experiences, and evaluation with the support of ICTs). Next are the digital competences related to research and professional development supported on the ICTs. The digital competences in which the Mexican university faculty is most proficient are those that are linked to the commitment and social responsibility of professors with the use of ICTs. It is concluded that there are priority training needs in line with the mid to low level of mastery of competences.